Strategies of Parents and Teachers in Form Positive Discipline Character of Students in Elementary School - Aini, Denada Nur; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: To find out how the strategies of teachers and parents to form students' positive discipline character in elementary school, to find out what are the supporting and inhibiting factors for the success of forming positive discipline character. Methodology: This study uses a qualitative research method with a phenomenological approach. The subjects targeted in this study are 3 parents who have preschool children in grades 4, 5, and 6 and teachers in grades 4, 5, and 6. Data collection techniques with observation, interviews, and documentation. The data analysis technique goes through three stages, namely data reduction, data presentation, and conclusion drawn. Results: Teachers' strategies in forming positive student discipline, namely by making school rules, providing punishment and rewards, and habituating. Meanwhile, parents' strategies are to apply rules at home, make the bed every morning, play with mobile phones not excessively, always accompany children to study, always remind children during prayer time. The supporting factors for the success of the formation of discipline character are by giving a little attention, giving praise or awards, always involving children in activities, communicating well; Give them examples of things that can shape positive discipline character. Factors that hinder the success of the formation of positive discipline character are not obeying the rules, parents and teachers cannot set an example, parents are busy, lack of attention. Applications/Originality/Value: Strategies used by teachers and parents have been proven to be able to shape the positive discipline character of elementary school students.